Concentrations of phthalate metabolites in Australian urine samples and their contribution to the per capita loads in wastewater - Tang, Shaoyu; He, Chang; Thai, Phong; Vijayasarathy, Soumini; Mackie, Rachel; Toms, Leisa-Maree L.; Thompson, Kristie; Hobson, Peter; Tscharke, Ben; O'Brien, Jake W.; Mueller, Jochen F. (Environment international, 2020)
•Urine and wastewater samples were collected from Southeast Queensland in 2012–2017.•14 phthalate metabolites were detected in urine and/or wastewater samples.•Urinary concentrations of MEP increased with age, while the other analytes decreased.•Concentrations of phthalate metabolites in wastewater were consistent over time.•Urinary excretion accounted for <50% of phthalate metabolites found in WWTPs. Exposure to phthalates is a public health concern. In this study, we collected both urine and wastewater samples from 2012 to 2017 and analysed for 14 phthalate metabolites to assess human exposure to phthalates in Southeast Queensland (SEQ), and for associations between phthalate metabolites in urine and wastewater samples. Twenty-four pooled urine samples were prepared from 2400 individual specimens every two years (stratified by age, gender and collection year). Wastewater samples were collected from the three major wastewater treatment plants (WWTPs) representing locations in the SEQ region including a regional city, part of the state capital city and a third major urban WWTP in the region. Over the period, decreases for most phthalate metabolites, i.e. mono-butyl phthalate (MBP), mono-isobutyl phthalate (MiBP), monobenzyl phthalate (MBzP), monocyclohexyl phthalate (MCHP), mono(3-carboxypropyl) phthalate (MCPP), mono(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP), mono(2-ethyl-5-oxohexyl) phthalate (MEOHP), and monomethyl phthalate (MMP), but an increase in monoethyl phthalate (MEP, particularly in young children) were observed in urine. In general, temporal changes were smaller in urine pools representing older age groups. We also found substantial variation in per capita mass loads of phthalate metabolites between samples from the three WWTPs with generally higher concentrations of most phthalates in the metropolitan areas. Per capita mass loads of most phthalate metabolites in wastewater were higher than would be expected from the per-capita excretion in urine, suggesting there are additional sources contributing to the majority of the observed phthalate metabolites in wastewater. For MEHHP and MEOHP we estimate that the urinary excretion accounts for a substantial fraction (average about 50%) of the mass load observed in the wastewater hence wastewater data may provide useful for monitoring trends in exposure.